SUSTAINABILITY PERFORMANCE, GREEN FINANCE AND FIRM VALUE: THE MODERATING EFFECT OF TAX PLANNING - Irawati; Melisa Fitrie; Ira Geraldina (CV. Radja Publika, 2026)
This study examines whether tax planning moderates the effect of sustainability performance on firm value in companies listed on the Indonesia Stock Exchange during 2020–2024. Using panel data from 58 companies selected through purposive sampling, this research applies a quantitative approach with Moderated Regression Analysis (MRA). The findings show that sustainability performance has a significant negative effect on firm value, while green finance has no significant effect. In addition, tax planning does not moderate the relationship between sustainability performance and firm value, nor does it strengthen the effect of green finance on firm value. These results indicate that investors may not immediately perceive sustainability and green finance initiatives as value-enhancing, particularly when their short-term economic benefits remain unclear. The study contributes to the literature on corporate sustainability, tax planning, and firm value in emerging markets.